Phosphorus Leaching in an Acid Tropical Soil “Recapitalized” with Phosphate Rock and Triple Superphosphate - Gikonyo, Esther Wakiuru; Abdul Rahman, Zaharah; Musa, Mohamed Hanafi; Abd Rahim, Anuar (2010)
“Phosphorus recapitalization” involves application of high phosphorus doses that could lead to P losses through leaching. Phosphate leaching was therefore tested on soils “recapitalized” with triple superphosphate (TSP) and Gafsa phosphate rock (GPR), but results of this work indicated there was high leaching in TSP treatments, particularly when it was integrated with manure, but there was no significant leaching in GPR even with manure integration. It is therefore agronomically and environmentally suitable to use PRs for “P recapitalization”.